PENERAPAN ARSITEKTUR BIOFILIK PADA PERANCANGAN SENTRA PERDAGANGAN IKAN DI KABUPATEN PINRANG - Rasyid, Andi Megawati; Bunawardi, Ratriana Said; Febriansyah, Muhammad Chaidar (TIMPALAJA : Architecture Student Journals, 2026)
Pinrang Regency has significant potential in the fisheries sector, particularly in pond aquaculture and marine products. However, this potential requires well-organized, healthy, and sustainable trading facilities. Fish trading activities contribute to local economic growth, but they may also create environmental, sanitation, circulation, and user-comfort problems if not properly planned. This study aims to design a Fish Trading Center in Pinrang Regency using a biophilic architectural approach to create a functional, comfortable, and environmentally responsive trading space. The method used is a descriptive-qualitative design method through literature studies, precedent studies, field surveys, site analysis, space requirement analysis, user activity analysis, and design concept synthesis. The design results show that the application of biophilic architecture is reflected in site planning that considers accessibility, separated entrance and exit circulation, pedestrian paths, parking areas, green open spaces, and the arrangement of main and supporting building masses. The biophilic concept is also applied through natural lighting, natural ventilation, vegetation, open spaces, natural materials, and visual connections between indoor spaces, outdoor spaces, and the surrounding environment. Therefore, this design is expected to support fish trading activities, improve user comfort, and strengthen the sustainable development of the fisheries sector in Pinrang Regency.